Peran Konseling Pastoral Dalam Pernikahan Anak Usia Dini Dibawah Umur 18 Tahun - Niskar Triheti Gea; Difly Praise Malelak; Etaning Putra Zai; Upi Yanti Gea; Fingka Sri Fornidian Hura (Lembaga Pengembangan Kinerja Dosen, 2023)
Early Childhood (AUD) is a social being who is in the age range of 0-8 years, the same thing is also stated by NAEYC. Early childhood is usually called the